Ex Vivo-expanded Natural Killer Cells Derived From Long-term Cryopreserved Cord Blood are Cytotoxic Against Primary Breast Cancer Cells. Issue 2 (February 2018) - Nham, Tina; Poznanski, Sophie M.; Fan, Isabella Y.; Vahedi, Fatemeh; Shenouda, Mira M.; Lee, Amanda J.; Chew, Marianne V.; Hogg, Richard T.; Lee, Dean A.; Ashkar, Ali A.
Abstract : With over 600, 000 units of umbilical cord blood (CB) stored on a global scale, it is important to elucidate the therapeutic abilities of this cryopreserved reservoir. In the advancing field of natural killer (NK) cell cancer immunotherapy, CB has proven to be a promising and noninvasive source of therapeutic NK cells. Although studies have proven the clinical efficacy of using long-term cryopreserved CB in the context of hematopoietic stem cell transplantations, little is known about its use for the ex vivo expansion of effector immune cells. Therefore, our group sought to derive ex vivo-expanded NK cells from long-term cryopreserved CB, using an artificial antigen presenting cell–mediated expansion technique. We compared the expansion potential and antitumor effector function of CB-derived NK (CB-NK) cells expanded from fresh (n=4), short-term cryopreserved (<1-year old, n=5), and long-term cryopreserved (1–10-year old, n=5) CB. Here, we demonstrated it is possible to obtain an exponential amount of expanded CB-NK cells from long-term cryopreserved CB. Ex vivo-expanded CB-NK cells had an increased surface expression of activating markers and showed potent antitumor function by producing robust levels of proinflammatory cytokines, interferon-γ, and tumor necrosis factor-α. Moreover, expanded CB-NK cells (n=3–5) demonstrated cytotoxicity towards primary breast cancer cells (n=2) derived from a triple-negative breast cancer and an estrogen receptor-positive/progesterone receptor-positive breast cancer patient. Long-term cryopreservation had no effect on the expansion potential or effector function of expanded CB-NK cells. Therefore, we propose that long-term cryopreserved CB remains clinically useful for the ex vivo expansion of therapeutic NK cells.